Light‐Mediated Multi‐Level Flexible Copper Iodide Resistive Random Access Memory for Forming‐Free, Ultra‐Low Power Data Storage Application. (28th November 2022) - Mishra, Dhananjay; Mokurala, Krishnaiah; Kumar, Ajit; Seo, Seung Gi; Jo, Hyeon Bin; Jin, Sung Hun
Abstract: This study demonstrates the efficacy of an emerging p‐type copper iodide (CuI) semiconductor in a flexible, low‐voltage resistive random‐access memory (RRAM), which can be readily integrated with metal‐oxide n‐type counterparts for complementary circuit systems. Herein, CuI RRAM devices are implemented via a room‐temperature solid iodination process, exhibiting a consistent On/Off ratio (≈10 4 ), excellent endurance of more than ≈10 3 cycles, together with a long retention period (> 5 × 10 4 s). Furthermore, a scheme of light‐mediated multi‐level data storage is demonstrated using blue light illumination (λ = 455 nm), to exploit possible photonic memristive functionality through notable photo‐response of CuI. In addition, the current conduction and resistive switching behaviors are systematically studied via low‐temperature measurements from 203 to 343 K, validating thermal stability and the governing key switching mechanism in CuI RRAM devices. The longstanding problem with CuI device longevity is effectively addressed via PMMA encapsulation, resulting in a 15‐fold improvement in the lifespan of devices even in air, as compared with non‐passivated devices. These findings suggest that flexible optoelectronic systems, combined with reliable, ultra‐low power CuI RRAM devices with photo memristive functionality, can leverage the enhancement of multifunctional selectors required in process‐in‐memories and the synaptic elements of neuromorphic applications. Abstract : CuI‐based (ITO/CuI/Ag) nonvolatile memory (NVM) devices are secured via vacuum‐driven solid iodination process, followed by PMMA encapsulation, enhancing longevity. The ITO/CuI/Ag devices exhibit decent resistive switching (RS) performance such as ultra‐low bias range (±0.5 V), high On/Off ratio (10 4 ), endurance (10 3 cycles), data retention 5 × 10 4 s, multi‐level data storage along with photo‐memristive functionality and flexible device implementation.